Mobility and Associated CO2 Emissions During and After COVID-19: A Case Study in Indonesia - Yusria Darma; Aidil Ambya Zula; M. Isya; Sugiarto Sugiarto; Muhammad Ahlan; Sofyan M. Saleh (International Journal of Disaster Management, 2023)
Changes in transportation trends can occur during and after COVID-19, such as travel distance, trip, and choice of transportation mode. The positive benefits from these changes in transportation trends should be maintained, to reduce disaster risk of environmental hazards from the CO2 emissions. Research on changes in mobility, trips, and CO2 emissions during and after COVID-19 in Indonesia is still very limited; whereas, changes in these transportation variables can be an inspiration for determining sustainable transportation policies in the future. This study aims to compare amid COVID-19 and post-COVID-19 transportation variables—travel distances, trips, and associated CO2 emissions. This research was conducted by giving questionnaires to 400 participants in Aceh Besar District. The questionnaire contains questions regarding the distance traveled, trips, fuel spent, and socio-economic characteristics. The CO2 emissions were calculated using IPCC (2006). The travel distance, trips, and transportation-related CO2 emissions during and after COVID-19 were compared respectively based on statistics. The results showed that there were significant differences in travel distances, trips, and transportation-related CO2 emissions between COVID-19 and the post-COVID-19 situation in the District of Aceh Besar. This article also presents several recommendations based on the data analysis results linked to literature studies about the sustainability of transportation as a result of COVID-19 situation; those are: providing quality public transportation, considering teleworking, providing solutions for workers who do not have access to online work, and paying attention to increasing use of private cars and car sharing post COVID-19.